PEMBANGUNAN KONSENSUS: SOLUSI PERENCANAAN DI BAWAH TEKANAN? - Ronny Bowo Leksono; Benedictus Kombaitan; Heru Purboyo Hidayat Putro; Haryo Winarso; Ridwan Sutriadi (Diponegoro University, 2019)
Planning in public domain in practice is seemingly seen as a utopian concept. Once the knowledge that becomes the basis of planning is built on the pure understandings to cope the problem objectively, in reality, it turns into inflexible and rigid approaches when dealing with various interests, namely political and social subjects. This is because of the distinct perspectives and understanding owned by people, the planning stakeholders which are divergent, and stirred by individual interest. What becomes an evident is that the plentiful of interest tends to trigger the opposite arguments. Accordingly, planning in public domain that hoped to have neutral position is like having a castle in the air, because the individual interests of the stakeholders of planning seems to be inseparable aspects. Planners are then required to have multi-skill of a wide range knowledge, indeed to find it like a search for demigods, albeit by involving many skill groups that ends on a new issue of integrating thinking. This article will therefore attempt to parse a possible problem resolution through the concept of consensus-building, by first explaining its relevance in the context of planning, complexity and commonly used methods, in order to achieve common goals of development, and thereby placing the planner and their plans becomes as a valuable works, its worhted.